Matching supply and demand - an integrated dynamic analysis of supply chain flexibility enablers - (:unkn) unknown (My University, 2025)
The increase of uncertainty of the market makes flexibility one of the most useful and necessary properties of modern manufacturing systems. This development causes challenging requirements for operations (processes) to match supply and demand. Flexibility has to be taken into consideration for resource development and finally market competitiveness under consideration of capacity, supply network, process technology, etc. Accurate theories on supply chain flexibility are therefore required for supply chain management. In particular the relations have to be investigated between flexibility, demand as well as supply uncertainty and companies’ performance. We propose to work out the dynamic dependencies existing between flexibility, forecasting accuracy and companies’ business performances at the supply chain level. In particular knowledge shall be generated about the level of flexibility required by companies with regard to demand uncertainties. The involved dependencies are only slightly understood, mainly due to the difficulty to analyze them dynamically at the entire supply chain level. Furthermore, the “right” performance measures for forecasting accuracy might not have been found yet in this complex, dynamic environment. The main questions we intend to answer are (1) How can the ideal level of flexibility be identified in a supply chain considering demand uncertainty? The final financial performance evaluation of the “ideal” flexibility should be based on resource costs, inventory related costs as well as customer related financial results (e.g. lost sales, financial impact of customer satisfaction). (2) How does the actual application of forecasting methods affect the overall performance of supply chain processes? We will conduct a quantitative model oriented research, especially under consideration of empirical data. Based on a conceptual framework integrating entire supply chain requirements, we will develop a system dynamic model that will be utilized to analyze propositions related to our research questions. The validation of the models will be done using dependency analysis supported by empirical data, i.e. GMRG database. Later, we will develop different supply chain models for at least three specific industries to be able to generalize our research results. This research project will contribute to improve knowledge on flexibility at the supply chain level, especially considering its relation to forecasting accuracy and companies’ business performances. This field is of importance for both academics and practitioners and results are therefore required to fill a gap in the literature as well as to support managers’ decisions.
Keywords: supply chain flexibility; performance measurement; Supply Chain Processes; Flexibility; Systems Dynamics; Forecasting